Angiotensin‐converting enzyme inhibitors reduce community‐acquired pneumonia hospitalization and mortality. Issue 12 (11th November 2022) - Alexander, Donald P.; Nickman, Nancy A.; Chhibber, Anindit; Stoddard, Gregory J.; Biskupiak, Joseph E.; Munger, Mark A.
Abstract: Background: Pneumonia is a global disorder and a common reason for prolonged hospitalization. Angiotensin‐converting enzyme inhibitors (ACEi) have pleiotropic effects that support a role in modulating pneumonia, but results have been controversial. Objectives: The present study was conducted to elucidate an ACEi‐induced pneumonia benefit in at‐risk neurologically impaired population and to determine whether a mortality benefit exists. Methods: A cohort study using a large health‐system of 29, 011 unique ACEi users and 1635 case patients 65 years of age or older without neurological disorders affecting swallowing who were admitted with community‐acquired pneumonia hospitalization and followed up from January 1, 2015 to December 31, 2019 (5 years). The association between ACEi use and pneumonia hospitalization and mortality were determined after propensity score matching using Cox and logistic regression. Results: The experimental cohort was 74.9 ± 7.3 years and 51% were male. ACEi users had lower odds of acquiring pneumonia versus ACEi non‐users (odds ratio) 0.72 [95% Confidence Interval (CI) 0.51 to 0.99]; p  = 0.048. The risk of short‐term mortality (<30 days) (HR) 0.42, p  < 0.001 and long‐term mortality (≥30 day) (HR) 0.83, p  < 0.002 was significantly lower for ACEi users compared with the ACEi non‐users. Conclusions: ACEi use in patients at risk of pneumonia without neurological swallowing disorders is associated with reduction in hospitalization and lowering of short‐ and long‐term mortality. Given the high incidence of morbidity and mortality associated with pneumonia, and the susceptibility in older populations with underlying cardiovascular or renal disease or social dependencies, our data support the prescribing of ACEi in these populations to reduce pneumonia hospitalization risk as well as short‐ and long‐term mortality.